The Atlantic's freshwater budget under climate change in the Community Earth System Model with strongly eddying oceans - A. Jüling; X. Zhang; D. Castellana; A. S. von der Heydt; H. A. Dijkstra (Ocean Science, 2021)
We investigate the freshwater budget of the Atlantic and Arctic oceans in coupled climate change simulations with the Community Earth System Model and compare a strongly eddying setup with 0.1 ∘ ocean grid spacing to a non-eddying 1 ∘ configuration typical of Coupled Model Intercomparison Project phase 6 (CMIP6) models. Details of this budget are important to understand the evolution of the Atlantic Meridional Overturning Circulation (AMOC) under climate change. We find that the slowdown of the AMOC in the year 2100 under the increasing CO 2 concentrations of the Representative Concentration Pathway 8.5 (RCP8.5) scenario is almost identical between both simulations. Also, the surface freshwater fluxes are similar in their mean and trend under climate change in both simulations. While the basin-scale total freshwater transport is similar between the simulations, significant local differences exist. The high-ocean-resolution simulation exhibits significantly reduced ocean state biases, notably in the salt distribution, due to an improved circulation. Mesoscale eddies contribute considerably to the freshwater and salt transport, in particular at the boundaries of the subtropical and subpolar gyres. Both simulations start in the single equilibrium AMOC regime according to a commonly used AMOC stability indicator and evolve towards the multiple equilibrium regime under climate change, but only the high-resolution simulation enters it due to the reduced biases in the freshwater budget.